New technology-based firms in the new millennium. Vol. 9 - Groen, Aard (Emerald, 2012)
This volume is the latest edition of an international edited book series based on the formation and growth problems of High Technology Small Firms (HTSFs) begun in 1993. This body of work is unique, and maps the evolution of research in this area through almost two decades of academic research and government policy towards a sector that is the key to future prosperity of developed and developing notational economies throughout the world. In this the latest Volume, there is one major and two subsidiary themes that have emerged from the best papers to be presented at the HTSF Conference held at the University of Twente at Enshede in May 2008. Following a contextual introduction by the editors, seven of the chapter are concerned with the key issue of strategy, which is always a key concern for HTSFs as they seek to find the best way to getting their products to the market. Indeed, a further two papers are concerned with the requirements of international marketing, while a final three papers deal with aspects of education for HTSF founders.
Keywords: High technology industries.; Small business -- Technological innovations.; New business enterprises.; Technological innovations -- Economic aspects.; elektronické knihy; electronic books